PENGARUH SIFAT MEKANIS BAHAN AISI 1045 YANG MENGALAMI PROSES DOUBLE HARDENING DAN CARBURIZING - Suhatta, Jefri; Priyagung, Priyagung; Marlina, Ena (Jurnal Teknik Mesin, 2015)
The role of steel in the world of today's automotive industry is very important, especially in the manufacture of automotive components such as gears. Surely it is necessary to materials engineering to improve the mechanical properties of the steel in order to obtain good quality. In engineering steel material commonly used is the heat treatment process, one of them with a carburizing process where in this process aims to add carbon to the outer skin steel.in research aimed at finding a material that resists wear and has the tenacity and hardness levels are good, then from that in this study in addition to carburizing process is also followed by a double hardening process. In this study carburizing process was conducted using the pack carburizing with charcoal were added barium carbonate as a catalyst, the temperature used is 9500 C and a holding time of 60 minutes, and followed with a double hardening process with temperature 9000 C and 7500 C with a holding time 20 minutes. After that, in the test with Vickers hardness test and impackcharpy test. The results of this study showed more upgrade hardness after carburizing process but toughness decreased. And after the double hardening hardness decreases but i toughness ncreased. Before treatment the average hardness value of steel and toughness 209.03 HVN and 0.8425 joules / mm2. The results of carburizing process average hardness value and toughness 417.13 HVN and 0.3975 joules / mm2. Results of a double process of hardening value the average hardness and toughness 308.5 HVN and 1.0974 joules / mm2. The results of the process of hardening II double the average value of hardness and toughness 243.63 HVN and 0.5728 joules / mm2.